Measurement of the morphological data of primary teeth in northwest China - Lu, Xiao-Xi; Yang, Kuan; Zhang, Bai-Ze; Wang, Jun-Hui; Du, Yang; Chen, Yu-Jiang; Wang, Xiao-Jing (Frontiers in Pediatrics, 2022)
Objective This study aims to digitally obtain the morphological data of children's primary teeth in northwest China and evaluate the reliability of digitally obtaining the anatomical morphological data of primary teeth. Methods A total of 308 extracted primary teeth and cone-beam computed tomography images of 407 primary teeth of northwest China were collected. Electronic digital vernier callipers were used to measure the mesiodistal and buccolingual diameters and crown length of the extracted primary teeth and calculate the crown area and crown index. Each sample was scanned with an intraoral scanner , and the resulting stl format files were imported into Geomagic Wrap 2015 to measure the axial and buccolingual diameters and crown length. The crown area and crown index were then calculated. After verifying the accuracy of the CBCT image measurement, the CBCT image data of 407 samples were measured in SmartV software using the ‘measure length’ function by referring to the coronal, sagittal and horizontal planes to adjust the position of the reference line. Results Northern Chinese have larger primary teeth than other populationsbut smaller primary teeth than native Australians. Compared to Indian primary teeth, northwest Chinese’s primary teeth have larger diameters on the central axis and smaller diameters on the buccolingual surface. Compared with the results of Wang Huiyun's study, the axial and buccolingual diameters and crown length of all native tooth types in this total sample were significantly smaller at the 0.1% level, and only the axial diameters of UD and LE and the crown length of LB were significantly smaller at the 1% level. The results of the intraclass correlation coefficient of 308 extracted primary teeth expressed an excellent degree of agreement between the callipers and intraoral scanner for the following: mesiodistal diameter , buccolingual diameter, crown length , crown index and crown area . Conclusion The digital measurements are in good agreement with the manual measurement of the vernier calliper. The difference between the anatomical morphology size of the primary teeth measured in this study and the results of different populations could be due to different genetic backgrounds and environmental factors.